2016
DOI: 10.1093/annonc/mdv381
|View full text |Cite
|
Sign up to set email alerts
|

Fruits, vegetables and lung cancer risk: a systematic review and meta-analysis

Abstract: Background: Lung cancer is the most common cause of cancer death. Fruits and vegetables containing carotenoids and other antioxidants have been hypothesized to decrease lung cancer risk. As part of the World Cancer Research Fund International Continuous Update Project, we conducted a systematic review and meta-analysis of prospective studies. Methods:We searched PubMed and several databases up to December 2014 for prospective studies. We conducted meta-analyses comparing the highest and lowest intakes and dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
119
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(137 citation statements)
references
References 58 publications
5
119
3
1
Order By: Relevance
“…With the exception of one study that only adjusted for age 31, all the studies included in our analysis were adjusted at least for smoking status, but there was not enough data to conduct subgroup analysis by smoking status. In the only study that showed separate results in smokers and never/former smokers 17, an inverse association with lung cancer mortality was observed for α ‐carotene and β ‐cryptoxanthin only in current smokers but not in never/former smokers, however, in a previous meta‐analysis of fruit and vegetable intakes (some of which are high in carotenoids) and lung cancer risk, we found similar summary RRs among never smokers as compared to current or former smokers 42, although power was more limited among never smokers as the number of cases was modest.…”
Section: Discussioncontrasting
confidence: 41%
“…With the exception of one study that only adjusted for age 31, all the studies included in our analysis were adjusted at least for smoking status, but there was not enough data to conduct subgroup analysis by smoking status. In the only study that showed separate results in smokers and never/former smokers 17, an inverse association with lung cancer mortality was observed for α ‐carotene and β ‐cryptoxanthin only in current smokers but not in never/former smokers, however, in a previous meta‐analysis of fruit and vegetable intakes (some of which are high in carotenoids) and lung cancer risk, we found similar summary RRs among never smokers as compared to current or former smokers 42, although power was more limited among never smokers as the number of cases was modest.…”
Section: Discussioncontrasting
confidence: 41%
“…Furthermore, physical activity levels are also associated with lower lung cancer mortality (low physical activity, hazard ratio (HR) 0.80 (0.69-0.92); medium physical activity, HR 0.68 (0.59-0.80); and high physical activity, HR 0.78 (0.66-0.93)) [9]. Similar evidences have been published regarding fruits and vegetables intake (RR 0.86; 95% CI 0.78-0.94) [10].…”
Section: Introductionsupporting
confidence: 60%
“…Because cigarette smoking accounts for 80% of the worldwide lung cancer burden in men and at least 50% of the burden in women, prevention the onset of smoking and successful smoking cessation strategies in current smokers will be the first effective measure in primary prevention of lung cancer [1,5]. Not smoking is the first strategy in preventing lung cancer [8].…”
Section: The Risky Diet and Lifestylementioning
confidence: 99%
“…While high-dose supplements of β-carotene have increased the lung cancer risk in male smokers due to aberrant cell growth in the respiratory epithelium [27], such finding does not exclude that a diet based on fruits, non-starchy vegetables and pulses (legumes), with a high content in vitamins, antioxidants and phytonutrients apart from β-carotene, in more balanced doses, may benefit in reducing lung cancer risk [8]. An illustrative example comes from a systematic review over the cruciferous vegetable (rich in isothiocyanates, like broccoli, cabbage and others) consumption and lung cancer risk conducted by Lam et al [28].…”
Section: The Risky Diet and Lifestylementioning
confidence: 99%
See 1 more Smart Citation